SEDIMENTASI DELTA SUNGAI CITARUM, KECAMATAN MUARA GEMBONG, KABUPATEN BEKASI (Sedimentation at Delta of Citarum River Muara Gembong District, Bekasi Regency) - Paryono Paryono; Ario Damar; Setyo Budi Susilo; Rokhmin Dahuri; Heny Suseno (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2017)
One of land use change impacts in the downstream of Citarum watershed is sedimentation. This study aimed to determine the total suspended solid and sediment load in the downstream of Citarum River. The Total Suspended Solid (TSS) samples were taken in three locations: the inlet of Jatiluhur reservoir, the outlet of Jatiluhur reservoir, and before the Citarum River estuary. The frequency of TSS samplings was twice a year i.e during the dry season and the rainy season at 2014. Analysis of TSS content was in accordance with SNI 06-6989.3-2004 using gravimetry method.  The results showed that TSS at down stream Citarum River flow was 0.44 kg/m3, TSS at the inlet of Jatiluhur reservoir was 0.20 kg/m3, and TSS at the outlet of Jatiluhur reservoir was 0.02kg/m3. The total sediment in the inlet of Jatiluhur was 1.34 x 106ton/year, in the outlet of Jatiluhur reservoir was 0.14 x 106ton/year, and the flow sediment total to the Citarum River estuary was 1.79 x 106 ton/year. The Jatiluhur reservoir could reduce the potential for sediment total flowing into the sea as much as 1.20x 106tons/year. Area of sedimentation at the delta of Citarum River was 3,828.26 ha.